2006
DOI: 10.1029/2006gc001316
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic processes in developing oceanic crust revealed in a cumulate xenolith collected at the East Pacific Rise, 9°50′N

Abstract: [1] The petrology and geochemistry of a xenolith, a fragment of a melt-bearing cumulate, within a recently erupted mid-ocean ridge (MOR) lava flow provide information on petrogenetic processes occurring within the newly forming oceanic crust beneath the northern East Pacific Rise (NEPR). The xenolith reveals important petrologic information about MOR magmatic systems concerning (1) melt distribution in a crystal-dominated mush; (2) melt-crystal reactions within the mush; (3) the chemistry of melts that have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 73 publications
(116 reference statements)
2
30
0
Order By: Relevance
“…Observations in the field and thin sections of clots of normal gabbros being smeared within anorthosite laminae suggest that a freshly settled layer of gabbro could have been dismembered and remobilized in an anorthosite‐rich suspension sweeping the floor. This interpretation may explain how anorthosite cumulates can be present as xenoliths in lavas extruded at EPR, fitting the conclusion of Ridley et al [2006] that they represent fragments from a melt‐bearing plagioclase cumulate.…”
Section: Discussionsupporting
confidence: 69%
“…Observations in the field and thin sections of clots of normal gabbros being smeared within anorthosite laminae suggest that a freshly settled layer of gabbro could have been dismembered and remobilized in an anorthosite‐rich suspension sweeping the floor. This interpretation may explain how anorthosite cumulates can be present as xenoliths in lavas extruded at EPR, fitting the conclusion of Ridley et al [2006] that they represent fragments from a melt‐bearing plagioclase cumulate.…”
Section: Discussionsupporting
confidence: 69%
“…In many cases it can be shown that mixing occurred within weeks to months before eruption (e.g., Pan and Batiza, 2002;Costa et al, 2009;Moore et al, 2014). Additionally, glomerophyric clusters of crystals, and small plutonic xenoliths containing interstitial melt, are found in some MORB suites (e.g., Hekinian et al, 1985;Ridley et al, 2006) suggesting disruption of mush zones accompanies eruption in some instances; this provides a mechanimsm for interstitial melt to be returned to an eruptible melt reservoir.…”
Section: Observational Constraints On Morb Differentiationmentioning
confidence: 99%
“…3) shows that interstitial melt within crystal mush zones at mid-ocean ridges can become highly fractionated. Evidence for disruption of such crystal mush zones prior to, and during, 20 eruptions come from the crystal cargo in MORB (e.g., Hekinian et al, 1985;Ridley et al, 2006;Costa et al, 2009;Moore et al, 2014) indicating that evolved interstitial melt must become mixed back into the eruptible magma reservoir. These observations lead us to explore whether in situ crystallization (Langmuir, 1989;Nielsen and DeLong, 1992;O'Hara and Fry, 1996b) can explain the observed differentiation trends in MORB.…”
Section: Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, primitive olivine crystals carried by evolved liquids have been interpreted as entrained macrocrysts in samples from Iceland (Thomson and Maclennan 2013), Hawai'i (Vinet and Higgins 2010), Réunion (Albarède and Tamagnan 1988), and mid-ocean ridges (Donaldson and Brown 1977). Basalt-hosted high-anorthite plagioclase macrocrysts have also been understood as disaggregated mush remnants in a range of geological settings (Hansen and Grönvold 2000;Ridley et al 2006). Moreover, isotope and trace element disequilibria between entrained macrocrysts and their carrier liquids indicate that crystals and melts are often derived from different mantle melt distributions (Halldórsson et al 2008;Winpenny and Maclennan 2011;Lange et al 2013b).…”
Section: Introductionmentioning
confidence: 99%